Blok IPFS Blockchain Untuk Orisinalitas Ijazah Pendidikan Tinggi - Rafly Putra Santoso; Rizky Rachman Judhie Putra (LKP KARYA PRIMA KURSUS, 2026)
Diploma fraud represents serious problem in Indonesian higher education threatening academic integrity. This research aims to design and build BlockIPFS prototype system and implement smart contract for diploma authenticity verification. Research method employs system development with stages including literature study, requirement analysis, three-tier architecture design, prototype construction using React and Node.js, DiplomaNFT smart contract implementation using Solidity, and validation testing. Prototype successfully implemented with architecture separating presentation layer (React), business logic layer (Node.js+Express), and data layer (Ethereum+IPFS). DiplomaNFT smart contract successfully deployed on Ganache with publishData() function for metadata storage, getStudentInfo() for data retrieval, and verifyDiploma() with two-factor verification mechanism using NIM and Diploma ID. System implements three-layer security: IPFS content-addressable storage with CID, blockchain immutability for metadata, and two-factor verification for access control. Testing demonstrates 0% data integrity error rate, 99.50% smart contract gas efficiency, and 100% content availability. Research contributions include cost-effective hybrid blockchain-IPFS architecture implementation, smart contract with dual-struct optimization, and two-factor verification mechanism that drastically improves security compared to single-factor systems.